The Representation of Islamic Educational Values in Katoba Tradition of Munanese Community - Ardianto Ardianto; Rokmina Gonibala; Hadirman Hadirman; Adri Lundeto (INNOVATIO: Journal for Religious Innovation Studies, 2020)
This article is the result of research that aims to explain the representation of Islamic educational values ​​in the Katoba tradition of the Munanese community. The object of observation is Katoba ritual. In-depth interviews were conducted with informants from the Katoba tradition practitioner which called imamu, academics, researchers, traditional and cultural leaders, educational practitioners, community leaders, and youth leaders. Provision of research data sourced from the results of recording, field notes and documents. This study found that the representation of the values ​​of Islamic education in the katoba tradition of Munanese community consists of the value of aqidah education, the value of religious education, and the value of moral education. Abstrak: Artikel ini merupakan hasil penelitian yang bertujuan untuk menjelaskan representasi nilai-nilai pendidikan Islam dalam tradisi Katoba pada masyarakat etnis Muna. Objek pengamatan adalah pelaksanaan ritual Katoba. Wawancara mendalam dilakukan dengan informan pengamal tradisi katoba yang disebut imamu, akademisi, peneliti, tokoh adat dan budaya, praktisi pendidikan, tokoh masyarakat, dan tokoh pemuda. Penyediaan data penelitian bersumber dari hasil pencatatan, catatan lapangan dan dokumen. Penelitian ini menemukan bahwa representasi nilai-nilai pendidikan Islam dalam tradisi katoba masyarakat etnis Muna terdiri dari nilai pendidikan aqidah / tauhid; nilai pendidikan agama; dan nilai pendidikan pendidikan moral.